2014
DOI: 10.1007/s11274-014-1768-z
|View full text |Cite
|
Sign up to set email alerts
|

Culturable diversity and functional annotation of psychrotrophic bacteria from cold desert of Leh Ladakh (India)

Abstract: To study culturable bacterial diversity under subzero temperature conditions and their possible functional annotation, soil and water samples from Leh Ladakh region were analysed. Ten different nutrient combinations were used to isolate the maximum possible culturable morphotypes. A total of 325 bacterial isolates were characterized employing 16S rDNA-Amplified Ribosomal DNA Restriction Analysis with three restriction endonucleases AluI, MspI and HaeIII, which led to formation of 23-40 groups for the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(62 citation statements)
references
References 39 publications
1
60
0
Order By: Relevance
“…There are very few reports of archaea as associated with plants such as maize, rice, and halophytic plant (Abutilon, Cressa, Sporobolus, and Suaeda nudiflora) [17][18][19]. Archaea have been reported as unculturable from maize [20] and rice crop [21], whereas culturable archaea have been reported from Abutilon, Cressa, Sporobolus, S. nudiflora [22] [17,23,24]. Microbiome of saline environments, especially halophilic fungi, has become one of the richest bioresources for industrially important molecules and enzymes.…”
Section: Biodiversity Of Halophilic Microbesmentioning
confidence: 99%
“…There are very few reports of archaea as associated with plants such as maize, rice, and halophytic plant (Abutilon, Cressa, Sporobolus, and Suaeda nudiflora) [17][18][19]. Archaea have been reported as unculturable from maize [20] and rice crop [21], whereas culturable archaea have been reported from Abutilon, Cressa, Sporobolus, S. nudiflora [22] [17,23,24]. Microbiome of saline environments, especially halophilic fungi, has become one of the richest bioresources for industrially important molecules and enzymes.…”
Section: Biodiversity Of Halophilic Microbesmentioning
confidence: 99%
“…Selvakumar et al (20) identified from the cold desert of Himalayan region by Yadav et al (21). In another study, Yadav et al (22) have reported and identified 11 psychrotrophic bacterial strains producing gibberelic acid. More than two dozens of wheat allied psychrotolerant bacterial strains producing gibberelic acid were isolated by Verma et al (3) from northern hills of India.…”
Section: Phytohormone Productionmentioning
confidence: 99%
“…Along with novel species of psychrotrophic microbes, some microbial species such as Arthrobacter nicotianae, Brevundimonas terrae, Paenibacillus tylopili, and Pseudomonas cedrina have been isolated and characterized for multifarious PGP attributes at low temperatures from cold deserts of NW Himalayas [7]. In a study by Yadav et al [8] [57].…”
Section: Biodiversity Of Beneficial Microbiomesmentioning
confidence: 99%
“…The haloarchaea have been isolated from many halophilic plants growing in hypersaline region of Rann of Kutch and characterized for different PGP attributes under hypersaline conditions [38,63,64]. In study by Yadav et al [8], …”
Section: Biodiversity Of Beneficial Microbiomesmentioning
confidence: 99%
See 1 more Smart Citation